Strategic Management Of Character Education For Enhancing Graduate Quality In Higher Education Institutions - Yudhie Suchyadi; Lina Novita; Rini Sri Indriani (Universitas Pakuan, 2026)
The quality of university graduates is increasingly determined not only by academic achievement but also by the integration of character values within institutional management systems. This study aims to analyze and develop an integrative model of character education management implemented in the Primary School Teacher Education Program (PGSD), Universitas Pakuan, Indonesia. The research employs a qualitative approach with a case study design to explore planning, implementation, supervision, and evaluation processes of character-based education management. Data were collected through in-depth interviews, participatory observation, and document analysis involving program leaders, lecturers, and students. Data analysis was conducted using interactive analysis techniques, including data reduction, data display, and conclusion drawing. The findings indicate that character education management in the PGSD Program is structured through three major pillars: academic excellence, professional ethics, and socio-cultural responsibility. The management model integrates character values into curriculum design, teaching-learning processes, co-curricular activities, and institutional governance. Strategic planning is aligned with the program’s vision and outcome-based education (OBE) framework, while supervision is conducted through continuous monitoring of student performance and behavioral indicators. The study reveals that a systemic-integrative approach to character education management contributes significantly to the development of high-quality graduates who demonstrate pedagogical competence, moral integrity, collaborative skills, and community engagement. This research offers a conceptual framework for strengthening graduate quality through institutionalized character education management in higher education settings.